AB0610 Platelet Factor 4 as A Biomarker in Korean Patients with Systemic Sclerosis. (15th July 2016) - Jung, K.H.; Park, W.; Kwon, S.; Lim, M.J.
Abstract : Background: Systemic sclerosis (SSc) is a complex multi-organ autoimmune disease with chronic and heterogeneous clinical manifestations. There is an unmet need for a new biomarker for early diagnosis and classification of SSc. Recent technical advancements have indicated several biomarkers for SSc; among these, platelet factor 4 (PF4), also known as CXCL4, was suggested by a large-cohort proteomic study 1 . PF4 is a chemokine released from activated platelets and is involved in coagulation, inflammation, and angiogenesis, which are influential in SSc pathogenesis. Therefore, PF4 may be an effective biomarker for SSc. Objectives: To investigate the efficacy of PF4 as a biomarker for the diagnosis, activity and severity of patients with SSc. Methods: Thirty-nine SSc patients (36 female and 3 male; mean age, 58.8±10.42 years; mean disease duration, 7.15±3.92 years; 11 diffuse cutaneous SSc cases and 28 limited cutaneous SSc cases) and 30 healthy controls (HC; 25 female and 5 male; mean age, 46.43±14.43 years) were enrolled. To estimate the circulating PF4 level, levels of platelet poor plasma (PPP) PF4 as well as serum PF4 were measured using an ELISA kit (R&D, Minneapolis, USA). SSc patients were divided into 2 subgroups according to disease activity and based on the presence/absence of interstitial lung disease (ILD), pulmonary hypertension, digital ulcers, and autoantibodies (anti-centromere Ab and anti-Scl70 Ab). Differences between SSc and HC groups were compared by Student's t -test, and the subgroups were compared using the Mann-Whitney test. Predictive values of serum PF4 and PPP PF4 for SSc diagnosis were evaluated by the area under the receiver operating characteristic curve (AUROC). Results: Serum PF4 levels of SSc were lower than those of HC (SSc, 5143.3±1777.5 ng/mL; HC, 5927.4±1348.5 ng/mL; p =0.048) but no significant differences were observed PPP PF4 levels (SSc, 407.2±486.6 ng/mL; HC, 297.3±141.5 ng/mL; p =0.187) between SSc patients and controls. Moreover, no significant differences were observed between active and inactive SSc subgroups and between subgroups with/without ILD, pulmonary hypertension, digital ulcers, and autoantibodies. The AUROC for serum PF4 and PPP PF4 levels was 0.628 (0.497–0.76, cuff of value 3998.5 ng/mL) and 0.491 (0.367–0.65, cuff of value 511.1 ng/mL), respectively. Conclusions: In Korean patients with SSc, both serum PF4 and PPP PF4 levels are not efficient biomarkers for SSc diagnosis and do not appear to be associated with clinical activity and severity. References: van Roon JA, Tesselaar K, Radstake TR. Proteome-wide analysis and CXCL4 in systemic sclerosis. N Engl J Med. 2014;370(16):1563–4. Disclosure of Interest: None declared